1998
DOI: 10.1016/s0378-1097(98)00445-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Streptococcus thermophilus strains by pulse field gel electrophoresis of genomic DNA

Abstract: Pulse field gel electrophoresis (PFGE) was utilised to compare the genomes of 16 Streptococcus thermophilus cultures from yoghurt, cheese, laban and dahi after digestion with the restriction endonucleases, SfiI, SmaI and BssHII. PFGE profiles could be used for strain identification and were also useful in predicting relatedness of certain strains. Genetic variations between specific morphotypes of a highly proteolytic culture were not detectable by PFGE in this study. Statistical analysis of SmaI restriction p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…helveticus clusters II and III contained only strains of the same acid production phenotype, but otherwise the clusters contained two or more phenotypes. O'Sullivan and Fitzgerald (1998) were able to associate acid production with two clusters of Strep. thermophilus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…helveticus clusters II and III contained only strains of the same acid production phenotype, but otherwise the clusters contained two or more phenotypes. O'Sullivan and Fitzgerald (1998) were able to associate acid production with two clusters of Strep. thermophilus .…”
Section: Discussionmentioning
confidence: 99%
“…The similarities reported here are consistent with those observed by authors investigating the same species with PFGE. O'Sullivan and Fitzgerald (1998) analysed Sma I genomic digestions by PFGE and found 39·53% similarity among 16 Strep. thermophilus strains.…”
Section: Discussionmentioning
confidence: 99%
“…Isolates that were confirmed to be S. thermophilus isolates were then analyzed by pulsed-field gel electrophoresis (PFGE) because of the lack of reliable PCR primers that could distinguish between the closely related species S. thermophilus and Streptococcus salivarius present in human oral cavity (28,34). Profiles of SmaI-digested chromosomes, obtained as described by O'Sullivan and Fitzgerald (25), were compared in order to determine strain identities.…”
Section: Bulgaricusmentioning
confidence: 99%
“…The ¢rst of which was to determine if the clumping phenotype was due to a large genetic re-arrangement which may have occurred as a consequence of the mitomycin C treatment. SmaI was chosen as a suitable enzyme for digestion of the DNA because work by Roussel et al [1] and O'Sullivan and Fitzgerald [2] had shown that restriction of S. thermophilus chromosomal DNA with SmaI resulted in 14^15 fragments greater than 30 kb. The numbers of genomic restriction fragments generated in S. thermophilus CNRZ1205 and its cured and re-lysogenised derivatives by SmaI appear to be less than those reported by other researchers [1,2] (Fig.…”
Section: Pulse ¢Eld Analysismentioning
confidence: 99%